2003
DOI: 10.1002/mrc.1273
|View full text |Cite
|
Sign up to set email alerts
|

Reorientational dynamics of two isomers of thiacalix[4]arene

Abstract: Molecular reorientation and local mobility of two isomers of 25,26,27,28-tetrapropoxy-2,8,14,20-tetrathiacalix[4]arene, cone and 1,3-alternate, were studied by means of NMR relaxation. The chemical shift anisotropy of 13 C nuclei was determined in the solid state. Nuclear relaxation due to dipole-dipole interaction and chemical shift anisotropy was analysed in the framework of the Lipari-Szabo approach. The aromatic core of both isomers was found rigid on the subnanosecond time scale. The amplitude of the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…As stated before, the O -propyl substituent is bulky enough to retard rotation of a phenol unit of the classical calix[4]arenes. Interestingly, however, it was found that the O -propylated phenol nucleus of 13 still retains the freedom to rotate, though very slowly, because 2 4 has a larger ring size than 3 4 . Thus, the 1,3-alternate conformer of 13 (the major product isolated from direct alkylation of 7 with propyl iodide) approached a conformational mixture of thermodynamic equilibrium containing four isomers after heating at 120 °C in CDCl 2 CDCl 2 solution for 4 months.…”
Section: 12 Conformational Behavior Of Alkylated Derivativesmentioning
confidence: 99%
“…As stated before, the O -propyl substituent is bulky enough to retard rotation of a phenol unit of the classical calix[4]arenes. Interestingly, however, it was found that the O -propylated phenol nucleus of 13 still retains the freedom to rotate, though very slowly, because 2 4 has a larger ring size than 3 4 . Thus, the 1,3-alternate conformer of 13 (the major product isolated from direct alkylation of 7 with propyl iodide) approached a conformational mixture of thermodynamic equilibrium containing four isomers after heating at 120 °C in CDCl 2 CDCl 2 solution for 4 months.…”
Section: 12 Conformational Behavior Of Alkylated Derivativesmentioning
confidence: 99%
“…13 The reorientational dynamics of calixarenes have been scarcely studied, 14 -16 with in-depth studies by 13 C NMR of calix [4]arene in chloroform and dimethyl sulfoxide 17 and of the cone and 1,3 alternate conformers of thiacalix [4]arene. 18 The dynamics of p-sulfonatocalix [4]arene have also been studied by 13 C NMR relaxation in aqueous and methanolic solutions, showing isotropic reorientational motion and Arrhenius behaviour in all cases. 19 In this work, the longitudinal relaxation times of the geminal methylene protons of p-sulfonatocalix [4]arene (Scheme 1) were used to probe the reorientational dynamics of the calixarene and of its 1 : 1 La(III) complex in aqueous solutions.…”
Section: Calix[n]arenesmentioning
confidence: 99%